Correlation among parents digital literation and children gadget usages and social behaviors - Salsabila Khoirun Nisa; Parji Parji; Muhammad Hanif (Prosiding Konferensi Ilmiah Dasar, 2020)
This study aims to describe the impact of the habits of students playing gadgets and understanding digital parental literacy on the social concerns of elementary school students in Madiun. This research uses a quantitative approach to the type of correlation study. Data sources used in this study are primary data sources and secondary data sources, while the data collection technique is to use a questionnaire, while secondary data are collected by observation, interview, and documentation instruments. Validation used to test the truth is the correlation test and triangulation of research sources. Data analysis uses the interactive model of Miles and Huberman.The research that has been done shows that 83% of students play gadgets with playing duration reaching more than 5 hours in one day, 17% of other students play gadgets with playing duration reaching 4 to 5 hours in one day. The habits of students playing gadgets are influenced by friends, family activities, and attention, the environment in which they live. Other negative effects due to the habit of playing online games affect the quality of sleep, eating patterns, and some children imitate the style of play that is played and practiced to peers in real life. The positive impact due to the habit of playing gadgets increases the vocabulary of foreign languages namely English. Negative impacts are more dominant due to the habit of playing online games